Regional Suppression of Bactrocera Fruit Flies (Diptera: Tephritidae) in the Pacific through Biological Control and Prospects for Future Introductions into Other Areas of the World - Roger I. Vargas; Luc Leblanc; Ernest J. Harris; Nicholas C. Manoukis (Insects, 2012)
Bactrocera fruit fly species are economically important throughout the Pacific. The USDA, ARS U.S. Pacific Basin Agricultural Research Center has been a world leader in promoting biological control of Bactrocera spp. that includes classical, augmentative, conservation and IPM approaches. In Hawaii, establishment of Bactrocera cucurbitae (Coquillett) in 1895 resulted in the introduction of the most successful parasitoid, Psyttalia fletcheri (Silvestri); similarly, establishment of Bactrocera dorsalis (Hendel) in 1945 resulted in the introduction of 32 natural enemies of which Fopius arisanus (Sonan), Diachasmimorpha longicaudata (Ashmead) and Fopius vandenboschi (Fullaway) were most successful. Hawaii has also been a source of parasitoids for fruit fly control throughout the Pacific region including Australia, Pacific Island Nations, Central and South America, not only for Bactrocera spp. but also for Ceratitis and Anastrepha spp. Most recently, in 2002, F. arisanus was introduced into French Polynesia where B. dorsalis had invaded in 1996. Establishment of D. longicaudata into the new world has been important to augmentative biological control releases against Anastrepha spp. With the rapid expansion of airline travel and global trade there has been an alarming spread of Bactrocera spp. into new areas of the world (i.e., South America and Africa). Results of studies in Hawaii and French Polynesia, support parasitoid introductions into South America and Africa, where B. carambolae and B. invadens, respectively, have become established. In addition, P. fletcheri is a candidate for biological control of B. cucurbitae in Africa. We review past and more recent successes against Bactrocera spp. and related tephritids, and outline simple rearing and release methods to facilitate this goal.